Microreticular perineurioma: A new morphological subtype of a rare entity. (12th March 2023) - Salah, Haneen T.; D'ardis, Julieta A.; Enos, Tyler; Klimas, Natasha; Gerber, Howard B.
Abstract: Perineurioma is a benign peripheral nerve sheath tumor. Several subtypes have been described, including plexiform, reticular, and sclerosing. The reticular variant has been previously described as having a net or lace‐like growth pattern consisting of large anastomosing cords of spindle‐shaped cells. We report a case of an 11‐year‐old male who presented with a 2‐year history of a slowly enlarging, tan‐white lesion on the finger. Microscopically, the lesion consisted of cells with ovoid nuclei and delicate, elongate cytoplasmic processes, arranged in a microreticular pattern. The lesional cells were markedly positive for epithelial membrane antigen and claudin‐1. Based on these features and the unusual morphology, the case was called a microreticular perineuroma. The patient underwent complete excision of the lesion with no recurrence 9 months after follow‐up. To our knowledge, this is the first reported case of this morphologic variant. Awareness of this entity is important to avoid inappropriate management.